Establishment and gene expression analysis of disease-derived induced pluripotent stem cells of scleroderma. Issue 2 (November 2016) - Wang, Zhongzhi; Nakamura, Kayo; Jinnin, Masatoshi; Kudo, Hideo; Goto, Mizuki; Era, Takumi; Kira, Tomomi; Nakashima, Taiji; Fukushima, Satoshi; Ihn, Hironobu
Highlights: We recently generated iPSCs from cultured dermal fibroblasts of systemic sclerosis (SSc-iPSC) to study the disease mechanisms. We performed gene expression analysis using SSc fibroblasts, SSc-iPSC, and fibroblasts re-differentiated from SSc-iPSC (SSc-iPSC-FB). We found constitutive and significant down-regulation of S100A8, Smad6, and TGF-β2 in SSc-iPSC. Expression of collagen, integrin α and β was up-regulated in SSc fibroblasts, while SSc-iPSC-FB showed normal levels of collagen and integrin β. Abstract: Background: We recently generated induced pluripotent stem cells (iPSCs) from cultured dermal fibroblasts of systemic sclerosis (SSc-iPSC) to study the disease mechanisms. Objective: In the present study, we have performed gene expression analysis using cultured SSc dermal fibroblasts, SSc-iPSC, and fibroblasts re-differentiated from SSc-iPSC (SSc-iPSC-FB). Methods: mRNA and protein levels of collagen and integrins were analyzed using PCR array, PCR, immunoblotting, and immunofluorescence. Results: We compared expression pattern of TGF-β-related genes between normal iPSC (NS-iPSC) and SSc-iPSC by PCR array, and found constitutive and significant down-regulation of S100A8, Smad6, and TGF-β2 in SSc-iPSC. The expression of these genes was not altered in cultured SSc fibroblasts or SSc-iPSC-FB compared to NS fibroblasts or NS-iPSC-FB, respectively. On the other hand, the expression of collagen, integrin α and β was up-regulated in SSc fibroblasts, while SSc-iPSC-FB showed normalized levels of collagen and integrin β. Conclusions: So far, there have been no reports investigating disease-derived iPSCs of SSc. Our results suggest that S100A8, Smad6, and TGF-β2 may be the key molecules of this disease. On the other hand, the normalization of collagen and integrins by iPSC reprogramming suggests that epigenetic modifications of genes may play a role in the mechanism of collagen accumulation seen in SSc fibroblasts, and that gene reprogramming may become novel therapeutic approach. As the limitation of this study, we established only one iPSC line from each patient, which may not be enough to discuss disease-specific phenotypes. Larger studies including increased number of iPSC lines are needed in the future.